Right Transverse Testicular Ectopia: A Nonclassified Variant Confirmed on Laparoscopy - Landry Mbouché; E. Njuma Tamufor; K. G. Fossi; A. S. Salihou; D. E. C. Dikongue; Salihou Fadi; Bienvenu Binwe; F. F. Mouafo Tambo (Case Reports in Urology, 2021)
Transverse testicular ectopia is a rare anomaly characterized by testicular descent into the scrotum through the same inguinal canal. Here, we report the case of a 15-year-old boy diagnosed with transverse testicular ectopia wherein both testes descended through separate inguinal canals. He underwent a diagnostic laparoscopy which helped to identify both spermatic cords entering both inguinal canals separately. During scrotal exploration, both testes were found in the same side. Transseptal orchidopexy was performed. The short-term follow-up is uneventful.